Analysis of marketing strategies in increasing sales volume in Alfamidi, Gido district: - Zega, Sadari; Gea, Nov Elhan; Batee, Maria Magdalena; Zebua, Serniati (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Alfamidi Gido District is a market that provides various kinds of fresh fruit such as grapes, lemons, melons, pears, watermelons and other fruit. Alfamidi Gido District is located in Hiliweto village Jln. Jalan Merdeka No. 89, Hiliweto Gido. This research aims to identify and find out marketing strategies in increasing the volume of fruit sales in Alfamidi, Gido District, to find out what Alfamidi's obstacles are in choosing a marketing strategy, and what Alfamidi's solutions are in choosing a marketing strategy. To achieve this goal, researchers processed data using descriptive qualitative research methods using observation, interviews and documentation research instruments and determined several respondents who had certain criteria: 1 key informant and 3 supporting informants. Based on the analysis above, conclusions can be drawn, namely in promoting Alfamidi fruit, Gido District has carried out a good and effective marketing strategy so that there has been an increase in sales of fresh fruit, where the main strategy is the marketing strategy. Based on the research results, it was concluded that a marketing strategy could increase the sales volume of Freshfruit in Alfamidi, Gido District.